Connection of the complex mathematical programming problem to quadratic programming problem - Jasilionis, R. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Ю. Ясилионис. Связь сложных задач математического программированы? с задачами квадратичного программированияR. Jasilionis. Sudėtingų matematinio programavimo uždavinių ryšys su kvadratinio programavimo uždaviniais